A study on permeability of soil cement / Panbarasi Govindasamy and Felix Ling Ngee Leh - Govindasamy, Panbarasi; Felix Ling, Ngee Leh (Universiti Teknologi MARA Cawangan Pahang, 2006)
Although there have been several research on engineering properties of residual soils in Malaysia, studies on the permeability properties of meta-sedimentary residual soils are still lacking. The objective of this study is to determine the influence of low percentage cement on permeability parameters of the meta-sedimentary soil. Samples of the residual soil were taken from Bangi, Selangor. Basic properties of soils, such as the natural water content, grain size distribution, specific gravity, and Atterberg limits were determined. Mainly, the coefficient of permeability of the soils both naturally and with those anticipated in the soil-cement modification is determined by using the Falling Head Permeability test. The results of analysis show that the permeability of low-cement admixed soil reduce as the quantity of cement increase. However, the addition of 10% cement gives an increased permeability value. The generated permeability parameters will indirectly become a guide in the preliminary soil cement stabilisation to modify the properties of the soil to become more like the properties of a soft rock.